Family – in the hierarchy of values of Piotrków students - Felchner, Andrzej (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
A few years ago Faculty of Social Sciences, Jan Kochanowski University, undertook a research concerning the hierarchy of values among our students. The aim was, not so much academic, as examining the priorities of those studying in the Piotrków branch of the University. The staff is concerned with improving educational processes. Besides, we have been trying to encourage our students’ interests by undertaking various cultural activities. We are aware that the majority of our students come from small towns and villages. In the near future they are going to be the first university graduates in their families. Their parents mainly have a secondary school diploma or vocational training. Our research confirmed the importance of family in our students’ hierarchy of values. This is an all-Poland tendency. Similar results were confirmed in other social groups. The present paper traces how the hierarchy of values developed in the researched group, and also examined their attitudes concerning some family related problems, for instance corporal punishment.
Keywords: values; youth; students; family